Implementasi Lingkungan Bahasa bagi Penutur Non Arab di Pesantren Modern - Cecep Sobar Rochmat; Nabielah Khusaini; Saiful Anwar; Mujib Abdurrahman (PALAPA, 2023)
Learning Arabic appears to be very difficult for non-native Arabic speakers, particularly beginners. The purpose of this study is to determine the application of the Arabic language environment for the New Santriwati in the Islamic Modern Boarding School Darussalam Gontor. The development and deployment of a language environment, which comprises types, programs, supporting components, and obstacles in the creation of language environments, is a crucial component of this research. This study employs qualitative and descriptive research methods, exposing methods based on the reality of actual situations and data-gathering treatments such as interviews, observations, and documentation. According to the outcome of this study, the environment of language is divided into two parts: formal and non-formal. The presence of a program of language activities such as ilqo' Mufrodat, idhof lughowi, arabic speaking, tasyji'u lugho, muhaawarah usbu'iyyah, fun friday, etc. The presence of figures/Qudwah in the Arabic language at all times is the most crucial component for encouraging the development of the linguistic environment. Obstacles encountered in implementing the language environment for the new santriwati at the Modern Darussalam Gontor consist of the differences in the background of students in Arabic learning, a lack of curiosity for Arabic vocabulary, a student's weak capacity in studying the Arabic language, and the presence of elements of underestimation to the disciplinary rules. The solution is to organize communication business activities, motivate people to love Arabic and tighten up Arabic language discipline. The findings of this study should assist teachers in developing a more conducive linguistic environment.